Effects of soluble surfactants on the deformation and breakup of stretching liquid bridges - Liao, Ying-Chih (Langmuir : the ACS journal of surfaces and colloids, 2004)
Surfactants are routinely used to control the breakup of drops and jets in many applications such as inkjet printing, crop spraying, and DNA or protein microarraying. The breakup of surfactant-free drops and jets has been extensively studied. By contrast, little is known about the closely related problem of interface rupture when surfactants are present. Solutions of a nonionic surfactant, pentaethylene glycol monododecyl ether, or C12E5, in water and in 90 wt % glycerol/water are used to show the effects of surfactant and viscosity on the deformation and breakup dynamics of stretching liquid bridges. Equilibrium surface tensions for both solutions can be fitted with the Langmuir-Szyskowski equation. All experiments have been done at 24 degrees C. The critical micelle concentrations for C12E5 are 0.04 and 0.4 mM in water and the glycerol/water solution, respectively. With high-speed imaging, the dynamic shapes of bridges held captive between two rods of 3.15 mm diameter are captured and analyzed with a time resolution of 0.1-1 ms. The bridge lengths are 3.15 mm initially and about 5-7 mm at pinch-off. Breakup occurs after stretching for about 0.2-0.3 s, depending on the solution viscosity and the surfactant concentration. When the liquid bridges break up, the volume of the sessile drop left on the bottom rod is about 3 times larger than that of the pendant drop left on the top rod. This asymmetry is due to gravity and is influenced by the equilibrium surface tensions. Surfactant-containing low-viscosity water bridges are shown to break up faster than surfactant-free ones because of the effect of gravity. With or without surfactant, water bridges form satellite drops. Surfactant-containing high-viscosity glycerol/water bridges break up more slowly than surfactant-free ones because of strong viscous effects. Moreover, the shapes of the sessile drops close to breakup exhibit a "pear-like" tip; whether a satellite forms depends on the surface age of the bridge before stretching commences. These unexpected effects arising from the addition of surfactants are due to the capillary pressure reduction and Marangoni flows linked to dynamic surface tension